2012
DOI: 10.1016/j.genm.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Androgen Deficiency Enhances Diet-Induced Hypercholesterolemia and Atherosclerosis in Low-Density Lipoprotein Receptor-Deficient Mice

Abstract: Background Despite numerous clinical and animal studies, the role of sex steroid hormones on lipoprotein metabolism and atherosclerosis remain controversial. Objective We sought to determine the effects of endogenous estrogen and testosterone on lipoprotein levels and atherosclerosis using mice fed a low-fat diet with no added cholesterol. Methods Male and female low-density lipoprotein receptor-deficient mice were fed an open stock low-fat diet (10% of kcals from fat) for 2, 4, or 17 weeks. Ovariectomy, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Female Cyp7a1 knockout mice have a threefold increase in hepatic cholesterol and increased cholesterol absorption while males have minimal increases in cholesterol absorption and hepatic cholesterol (12). Higher cholesterol was found in female compared to male LDL-receptor knockout mice fed a low-fat chow (17). Furthermore, orchidectomy increased cholesterol in males but ovariectomy did not alter 3.6 ± 0.6* 6.8 ± 1.8* † Hepatic triglycerides (nmol/100 mg liver weight) 16 ± 6 22 ± 6 20 ± 7 17 ± 12 23 ± 5 27 ± 3* Serum for lipid panels was allowed to clot at room temperature for 30 min prior to separation and analysis at ARUP laboratories.…”
Section: Articlesmentioning
confidence: 94%
See 2 more Smart Citations
“…Female Cyp7a1 knockout mice have a threefold increase in hepatic cholesterol and increased cholesterol absorption while males have minimal increases in cholesterol absorption and hepatic cholesterol (12). Higher cholesterol was found in female compared to male LDL-receptor knockout mice fed a low-fat chow (17). Furthermore, orchidectomy increased cholesterol in males but ovariectomy did not alter 3.6 ± 0.6* 6.8 ± 1.8* † Hepatic triglycerides (nmol/100 mg liver weight) 16 ± 6 22 ± 6 20 ± 7 17 ± 12 23 ± 5 27 ± 3* Serum for lipid panels was allowed to clot at room temperature for 30 min prior to separation and analysis at ARUP laboratories.…”
Section: Articlesmentioning
confidence: 94%
“…cholesterol in females (17). Androgen levels may be protective for hypercholesterolemia, and dietary fat and cholesterol may interplay with sex steroids to alter cholesterol metabolism (17).…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Castrated animals showed a further elevation in VLDL that combined with their reduced HDL levels ( Fig. 2A, C ) may provide a mechanistic interpretation of the results of a recent study showing that castrated Ldlr Ϫ / Ϫ mice fed a low-fat diet develop more severe atherosclerotic lesions than sham-operated animals ( 50 ). At fi rst glance, it may appear that the reduction in plasma HDL levels is insignifi cant because sham-operated mice already have reduced HDL levels compared with control C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 59%
“…Clinical studies reported that testosterone levels inversely correlated with total cholesterol and LDL cholesterol levels [11][12][13] . In addition, animal studies demonstrated highly elevated cholesterol levels in testosterone-deficient male mice 14,15 . These findings suggested that testosterone serves a valuable role in regulating serum lipids.…”
Section: Introductionmentioning
confidence: 99%